Strengthening Parental Involvement in Improving Children’s Reading Interest through a Home Literacy Program - Endi Rochaendi; Marta Romero (Journal of Community Action, 2026)
Children’s reading interest is a fundamental component of early literacy development and long-term academic success. Previous studies consistently indicate that parental involvement plays a decisive role in shaping children’s reading motivation and literacy achievement. This article aims to examine how strengthening parental involvement through a structured Home Literacy Program can improve children’s reading interest. Employing a mixed-methods approach, this study involved 120 elementary school students and their parents from three urban schools. Quantitative data were collected through reading interest questionnaires and parental involvement scales, while qualitative data were obtained through interviews and observation logs. The findings reveal that children whose parents actively participated in home-based literacy activities demonstrated significantly higher reading interest, motivation, and engagement compared to those in the control group. Moreover, parents reported improved confidence and awareness in supporting their children’s literacy development. These findings align with previous research emphasizing the importance of home–school partnerships and family literacy interventions. The study concludes that a well-designed Home Literacy Program can serve as an effective strategy for strengthening parental involvement and fostering sustainable reading interest among children.